Epigenetic Modifications in Stress Response Genes Associated With Childhood Trauma - Jiang, Shui; Postovit, Lynne; Cattaneo, Annamaria; Binder, Elisabeth B.; Aitchison, Katherine J. (Frontiers in Psychiatry, 2019)
Adverse childhood experiences (ACEs) may be referred to by other terms (e.g., early life adversity or stress and childhood trauma) and have a lifelong impact on mental and physical health. For example, ACEs have been associated with post-traumatic stress disorder (PTSD), anxiety, depression, bipolar disorder, diabetes and cardiovascular disease. The heritability of ACE-related phenotypes such as PTSD, depression and resilience is low to moderate, and, moreover, is very variable for a given phenotype, which implies that gene by environment interactions (such as through epigenetic modifications) might be involved in the onset of these phenotypes. Currently, there is increasing interest in the investigation of epigenetic contributions to ACE-induced differential health outcomes. Although there are a number of studies in this field, there are still research gaps. In this review, the basic concept of epigenetic modifications (such as methylation) and the function of the hypothalamo–pituitary–adrenal (HPA) axis in the stress response is outlined. Examples of specific genes undergoing methylation association with ACE-induced differential health outcomes are provided. Limitations in this field, e.g., uncertain clinical diagnosis, conceptual inconsistencies, and technical drawbacks are reviewed, with suggestions for advances using new technologies and novel research directions. We thereby provide a platform on which the field of ACE-induced phenotypes in mental health may build.